NARRATIVE TEXT DEVELOPMENT AMONG NON-ENGLISH UNIVERSITY STUDENTS AT LUBUKLINGGAU, INDONESIA - Astri Riance (Journal of Language, Literature and Teaching, 2020)
The aims of this study was to know narrative text development among non English University students at Lubuklinggau. This study focused on writing narrative text by using generic structure and grammatical feature. This research was conducted at the first semester students of accounting Bina Insan University Lubuklinggau. Based on the data analysis from the test which was given to the students, can be concluded that. The students correct answer in grammatical feature was 46,33%, in orientation was 74%, in evaluation was 53,16%, in complication was 56,83% and in resolution was 58,83%. It means that the students ability in writing narrative text reviewed from generic structure and grammatical feature is still low. The result of the students test is also can be seen from the students score skill level, there are 16 students in low level and 14 students in medium level. And the average of students score was 57.7. From the result of the test above, the researcher concluded that the students development in writing narrative text is still low, they are still confuse about the rule in writing narrative text, such as about grammatical feature and Generic Structure. therefore teachers have to find creative techniques and good methods in teaching narrative text, in order to students will be more interested and understend when teaching and learning process occurs. Keywords: Writing, Narrative Text, Generic Structure, Grammatical Feature